Stability of an extemporaneously compounded minoxidil oral suspension. (1st March 2018) - Song, Yunmei; Chin, Zen Whey; Ellis, David; Lwin, Ei Mon Phyo; Turner, Sean; Williams, Desmond; Garg, Sanjay
Abstract : Purpose: Results of a study to determine the stability of an extemporaneously compounded minoxidil oral suspension under various temperature and stress conditions are reported. Methods: Commercially available minoxidil tablets (10 mg) were crushed to a fine powder, and predetermined amounts of 2 suspending vehicles were added to produce a 1-mg/mL suspension, which was stored in glass bottles at room temperature (25 ± 2 °C) or in a refrigerator (4 ± 2 °C). To simulate daily patient use, 5 days weekly 1 bottle of the suspension was removed from refrigerated storage and shaken and 0.5 mL of the contents discarded. At each specified time point, samples were analyzed in duplicate ( n = 6 for each test condition) using a validated high-performance liquid chromatography method. Samples were visually observed and their pH measured at each time point. Microbiological studies were performed on day 0 and at week 24. Results: The mean percentage of initial minoxidil concentration remaining in all refrigerated samples exceeded 90% throughout the 24-week study, with no change in appearance, pH, microbial activity, odor, or redispersibility. During storage at room temperature, the suspension exhibited a color change at week 4, with slight sedimentation after 6 weeks, although minoxidil recovery exceeded 90% for 10 weeks. Conclusion: An extemporaneously compounded minoxidil oral suspension was stable for 24 weeks when stored in a refrigerator. This suspension can be used for up to 3 weeks when stored at room temperature.